Sensitivity analysis of the value function for infinite dimensional optimal control problems and its relation to Riccati equations. (2nd September 2018) - Guglielmi, Roberto; Kunisch, Karl
Abstract: First and second order sensitivities of the value function in optimal control problems constrained by semilinear parabolic equations with respect to the initial condition are considered. Sufficient conditions are given which allow to express these sensitivities in terms of the adjoint equation and a suitably defined Riccati equation.